The Intervening Effect of Current Knowledge Enhancement on Attitude and Intention to Choose Accounting Career - Saarce Elsye Hatane; Felicia Jesslyn Setiono (Binus Business Review, 2019)
The purpose of this research was to examine the influence of attitude in accounting students to the intention to choose an accounting career. It was through the intention to increase current knowledge as an intervening variable. This research used a survey online method to test the research model, which was responded by a total of 503 accounting students across Java. Data analysis and hypothesis testing used partial least square as part of the structural equation model technique. According to their ages, the respondents were famous as the millennial generation in this era. The results of this research are in accordance with the Theory of Planned Behavior (TPB). It is proven that attitudes have a positive and significant influence on the intentions of accounting students in terms of increasing current knowledge and choosing accounting careers. This research also supports the Social Cognitive Career Theory (SCCT). There is evidence that educational background and learning experience can increase the intention of accounting students to pursue careers in accounting. The existence of different generations leads to different perceptions of students regarding accounting careers. Therefore, further research is needed to identify these differences. The results also suggest that accounting educators need to update their curriculum by adapting the current development and demands of graduates. Last, the rapid development of technology has had a significant influence on the accounting profession.